Renaissance Naples : a documentary history, 1400/1600 - Nichols, Charlotte, 1954-; McGregor, James H. (James Harvey), 1946- (Documentary history of Naples., 2018)
"An introduction to the development of the city of Naples from the end of the Angevin period in 1400 to 1600, with a collection of English-language sources on the history of the city covering its economic, literary, artistic, religious and cultural life "--